(untitled) (Research, Society and Development, 2021)
Objective: To describe the skills developed by the members of a group tutorial of PET-Health Interprofessionality, based on the actions carried out in the first year of implementation of the Project. Method: This is a descriptive study of the experience report type, developed by PET tutorial group of Sobral city, in which is linked to the Vale do Acaraú State University, Federal University of Ceará and the School of Public Health Visconde de Sabóia, through the Sobral Health Department. The Experience portrays the actions developed by 14 members, Wich is formed by two tutors, four preceptors and eight monitors from the courses of Nursing, Physical Education, Medicine, Dentistry and Psychology, through conversation groups in the tutorial group, where a revision was made to the Pet Health Interprofessionality Project Sobral and the semiannual report, listing the competencies identified and classifying them into specific, common and collaborative, systematizing the information in a chart. Results: The experience of integrating different formations it became possible to identify the actions developed in a perceptible way, where it was manifested by the monitors, preceptors and tutors in the reports of actions and classify them according to the competencies: specific, common and collaborative, developed with students and health professionals. Conclusion: With the current participation of PET- Health - Interprofessional, the guidelines of the competencies were potentiated in the midst of the actions carried out by participants among themselves and together with the health system. Therefore, it is of relevance in interprofessional practice, that the ideals of competences are implemented fully from the perspective of interprofessionality, facilitating and strengthening the collaborative work.